The Influence of Transformational Leadership Style and Competence on Employee Performance At the Secretariat of the Regional People's Representative Council of Selayar Islands Regency - Andi Marina (Yayasan Amerta Insan Unggul, 2023)
This research aims to determine the influence of transformational leadership style and competency on employee performance. The research used a quantitative type approach. The data processed is the result of respondents' interpretation from employees of the Selayar Islands Regency Regional People's Representative Council Secretariat. The data collection methods used in this research are observation, questionnaires and documentation. The population and sample used in this research were 94 respondents. The results of this research show that the Transformational Leadership Style has a positive and significant effect on Employee Performance at the Selayar Islands Regency DPRD Secretariat as evidenced by the results of data processing, where the calculated t value is 4,341 > the T table value is 1.98667 and the significance value is 0.000 < 0.05. And competency has a positive and significant effect on employee performance at the Selayar Islands Regency DPRD Secretariat as evidenced by the results of data processing, where the calculated t value is 4,333 > t table value of 1.98667 and the significance value is 0.000 < 0.05.